Development of electrocoagulation process for wastewater treatment: optimization by response surface methodology. Issue 5 (May 2022) - Ebba, Million; Asaithambi, Perumal; Alemayehu, Esayas
Abstract: Electrocoagulation (EC) is a process used by supply of electric current with sacrificial electrodes for the removal of pollutant from wastewater. The study was experimentally investigated taking into account various factors such as pH (3–7.5), current (0.03–0.09 A), distance between the electrodes (1–2 cm), electrolytic concentration (1–3 g/L), and electrolysis time (20–60 min) which is impact on the % removal efficiency of color, chemical oxygen demand (COD), turbidity and determination of energy consumption used for aluminum (Al) electrode used. The surface response design process based on the central composite design (CCD) has been used to optimize different operational parameters for treatment of hospital wastewater using EC process. The % color, COD and turbidity removal, and energy consumption under different conditions were predicted with the aid of a quadratic model, as were the significance and their interaction with independent variables assessed by analysis of variance (ANOVA). The optimal conditions were obtained through mathematical and statistical methods to reach maximum % color, COD, and turbidity removal with minimum energy consumption. The results showed that the maximum removal of color (92.30%), COD (95.28%), and turbidity (83.33%) were achieved at pH–7.5, current–0.09A, electrolytic concentration–3g/L, distance between electrodes–2 cm and reaction time 60 min. This means that, the process of EC can remove pollutants from various types of wastewaters and industrial effluent under the various operating parameters. Graphical abstract: Image 1 Highlights: EC effective technology used to treat wastewater generated from hospital. Al was used as an electrode for hospital wastewater treatment using EC process. EC can eliminate pollutants from wastewater under various operating parameters. CCD used to optimize operational parameters for treatment of hospital wastewater. Abstract : Electrocoagulation; hospital wastewater; color, COD and turbidity removal; energy consumption; optimization; RSM.